A Growth Model for a Tenured-Labor-Managed Firm: Comment - de Meza, David (Quarterly Journal of Economics, 1983)
Journal Article A Growth Model for a Tenured-labor-managed Firm: Comment Get access David de Meza David de Meza London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 98, Issue 3, August 1983, Pages 539–542, https://doi.org/10.2307/1886028 Published: 01 August 1983